From popular to insurgent intellectuals peasant catechists in the Salvadoran revolution - Binford, Arthur Leigh 1948- (New Brunswick, NJ Rutgers University Press, 2022)
From Popular to Insurgent Intellectuals explains how a group of Catholic lay catechists educated in liberation theology came to take up arms and participate on the side of the rebel FMLN during El Salvador’s revolutionary war (1980-92). In the process they became transformed from popular intellectuals to insurgent intellectuals who put their organizational and cognitive skills at the service of a collective effort to create a more egalitarian and democratic society. The book highlights the key roles that peasant catechists in northern Morazán played in disseminating liberation theology before the war and supporting the FMLN during it—as quartermasters, political activists, and musicians, among other roles. Throughout, From Popular to Insurgent Intellectuals highlights the dialectical nature of relations between Catholic priests and urban revolutionaries, among others, in which the latter learned from the former and vice-versa. Peasant catechists proved capable at making independent decisions based on assessment of their needs and did not simply follow the dictates of those with superior authority, and played an important role for the duration of the twelve-year military conflict
About the Author
In English
Keywords: Catholics -- Political activity -- El Salvador -- History -- 20th century; Liberation Theology -- El Salvador; HISTORY / General; Farabundo Martí Front for National Liberation, El Salvador, El Salvador politics, Christianity in South America, catechists, El Salvador civil war, wartime South America, South American Wars, wars in South America, religious war, peasant catechists, activism, religious activism, political activism, social justice struggles, El Mozote, El Castaño, Northern Morazán, The Ligas Populares, religion in South America, Catholicism, social activism, urban revolutionaries, Salvadorian 12 year war, the 12 year war, Latin American empowerment, Hispanic Empowerment